2011
DOI: 10.1111/j.1651-2227.2011.02437.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and pattern of hearing impairment in children with ≤ 800 g birthweight in British Columbia, Canada

Abstract: The incidence and severity of hearing impairment in a cohort of extremely low-birthweight children increased significantly from 5% to 13% (p = 0.01) over a 24-year period. Comorbidities were common. Potentially modifiable causes are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…Initial database searches identified 6964 potential articles with 18 included in the review (Figure 1). Of these, 11 focused on diagnostic methods and schedules (Table 1), [35][36][37][38][39][40][41][42][43][44][45] 4 investigated the impact of cerebral palsy on hearing loss assessment and diagnosis, [46][47][48][49] and 3 reported on intervention or rehabilitation for infants with or at high risk for cerebral palsy. [50][51][52] Sample size ranged from 13 to 40 723 infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial database searches identified 6964 potential articles with 18 included in the review (Figure 1). Of these, 11 focused on diagnostic methods and schedules (Table 1), [35][36][37][38][39][40][41][42][43][44][45] 4 investigated the impact of cerebral palsy on hearing loss assessment and diagnosis, [46][47][48][49] and 3 reported on intervention or rehabilitation for infants with or at high risk for cerebral palsy. [50][51][52] Sample size ranged from 13 to 40 723 infants.…”
Section: Resultsmentioning
confidence: 99%
“…Threshold cutoff for diagnosing hearing impairment varied across studies, from 25 to 40 dB normal hearing level or electrophysiologic level (nHL) (electrophysiologic thresholds). Degree of hearing impairment varied, with some authors reporting on moderate to profound hearing loss, 37,39,42,44 whereas others included all impairments, even potential ones 40,43,45,47,48 (Table 1). Overall, risk of bias in this category was low, with most studies providing appropriate level of detail in protocol, outcome measures, and analysis descriptions.…”
Section: Schedules and Methods For Hearing Loss Diagnosismentioning
confidence: 99%
“…In NICHD Phototherapy Trial, rates of bilateral hearing impairment with amplification were 1% in the aggressive phototherapy arm and 3% in the conservative phototherapy arm ( 12 ). In a Canadian study of preterm infants ≤800 g, the overall rate of bilateral permanent HL was 9% (50/586 infants) ( 13 ) and rates of permanent bilateral hearing loss were higher at lower gestational age ( 14 ). Based on these estimates of prevalence, hearing impairment would be the third most prevalent major developmental impairment identifiable during infancy among extremely low birth weight infants after cognitive impairment and cerebral palsy ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…As these infants are identified as being at-risk for progressive or late-onset hearing loss, it is essential that they are not only screened at birth, but are followed regularly for audiological assessment and are not lost to follow-up. [7] The High-Risk Register Use of the HRR as the primary indicator for screening of newborns for hearing loss was inadequate. In 1999, Finitzio and Crumley reported that, according to the identification rates currently reported from widespread screening programs, approximately 8,000-16,000 newborns are born with hearing loss each year.…”
Section: Prevalence Of Hearing Lossmentioning
confidence: 99%